The Use of Mobile Phone as Teaching Aid On EFL Students’ Speaking Performance and Perception - M. Adieb H; Johannes A Prayogo; Ekaning Dewanti Laksmi (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This paper presents the effect of Mobile Phone on EFL Students’ speaking performance and perception. While mobile phone has been utilized beyond its primary use as a communication tool, there are only a limited number of studies in pedagogy which highlights the importance of mobile phone in teaching-learning activities. The objective of this paper is to show the effect of Mobile Phone as teaching aid on EFL Students’ speaking performance and perception. The result of this study shows students who taught using mobile phone outperformed students who taught by conventional teaching.Abstrak: Penelitian ini berisi tentang pengaruh dari mobile phone terhadap kemampuan bahasa Inggris dan persepsi dari siswa. Banyak kegunaan mobile phone selain sebagai alat komunikasi, namun hanya sedikit yang membahas kegunaan mobile phone di dalam kegiatan belajar mengajar. Penelitian ini bertujuan untuk melihat pengaruh dari mobile phone sebagai bahan bantu pengajaran terhadap kemampuan berbicara siswa. Hasil dari penelitian ini menunjukkan siswa yang belajar dengan menggunakan mobile Phone memiliki pencapain yang lebih baik daripada siswa yang belajar menggunakan cara konvensional.